2002
DOI: 10.1111/1469-7610.00036
|View full text |Cite
|
Sign up to set email alerts
|

Energy compensation in young children who fail to thrive

Abstract: The controls compensated as expected for their high energy load at the subsequent meal, but the case children did not, showing that they lack the normal responses to internal hunger/satiation cues. High energy snacks may improve the nutritional status of children who fail to thrive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“…Similarly, only between 5 and 10% will have any symptoms or signs of underlying disease (14) . Some evidence of differences in maternal feeding behaviour and appetite and eating behaviour as well as decreased energy intake at meals (31) have been found in the infant (27)(28)(29)(30) . Thus, the majority of children showing a weight faltering pattern have no observable disease or evidence of neglect.…”
Section: Failure To Thrive/weight Falteringmentioning
confidence: 99%
“…Similarly, only between 5 and 10% will have any symptoms or signs of underlying disease (14) . Some evidence of differences in maternal feeding behaviour and appetite and eating behaviour as well as decreased energy intake at meals (31) have been found in the infant (27)(28)(29)(30) . Thus, the majority of children showing a weight faltering pattern have no observable disease or evidence of neglect.…”
Section: Failure To Thrive/weight Falteringmentioning
confidence: 99%
“…On average, after a high energy preload, infants and preschool children reduce their meal intake by between 50% and 100% (Birch & Deysher, 1986;Johnson & Birch, 1994) of the energy content of that preload, but older children compensate much less (Cecil et al, 2005;Johnson & Taylor-Holloway, 2006). Only one previous study has examined energy regulation in a clinical group; this study (Kasese-Hara, Wright, & Drewett, 2002) found that weight-faltering children seemed not to compensate; they ate the same, smaller amount after both high and low energy preload. No studies have yet formally assessed energy regulation in enterally fed children.…”
Section: Introductionmentioning
confidence: 97%
“…Similarly, there are infants who are described as 'contented' after very small feeds, and who do not wake up for feeds, who also fail to thrive (Davies, 1979). These infants are similar to those who fail to show compensation in their energy intake when given a high-calorie preload before a meal (Kasese-Hara et al, 2002). Such children show poor appetite regulation and for this reason fail to take in sufficient calories to accord with growth requirements.…”
Section: Child Factorsmentioning
confidence: 99%